Catalytic conversion of methane and carbon dioxide in conventional fixed bed and dielectric barrier discharge plasma reactors - Istadi, Istadi (2006)
The natural gases in the Natuna and Arun fields have CO2/CH4 ratio being 71/28 and 15/75, respectively. These ratios are potential for the production of C2+ hydrocarbons and synthesis gas. The purpose of this study is to develop a new catalytic process for CH4 and CO2 utilization to produce C2 hydrocarbons and/or synthesis gas at high conversion and selectivity. The studies started with a thermodynamic equilibrium analysis of CH4 and CO2 reactions to produce C2 hydrocarbons and synthesis gas in order to investigate the feasibility of the reactions thermodynamically. The results showed that carbon dioxide reforming of methane, reverse water gas shift reaction, and dehydrogenation of ethane to ethylene were more viable than CO2 oxidative coupling of methane. In the catalytic system, CeO2- based catalyst screening was performed. The CaO-MnO/CeO2 catalyst system displayed high stability suitable for the CO2 oxidative coupling of methane. Moreover, the operating parameters, such as the CO2/CH4 feed ratio and reactor temperature, and the catalyst compositions, such as wt% CaO and wt% MnO, were optimized by using Weighted Sum of Squared Objective Functions algorithm. The synergistic effect of basicity and reducibility towards the catalytic activity were also addressed using XRD, CO2-TPD and H2-TPR. The synergistic effect of catalyst basicity and reducibility are vital in enhancing the reaction performance. Since the conversion and yield were still low, the conventional CO2 oxidative coupling of methane was replaced with a more advanced reactor. The hybrid catalytic dielectricbarrier discharge plasma reactor was utilized for the synthesis gas and C2+ hydrocarbons (ethane, ethylene, acetylene, and propane) production in one step. The new reactor system displayed promising performance at low temperature over CaOMnO/ CeO2 catalyst. Next, a hybrid Artificial Neural Network – Genetic Algorithm technique was used to facilitate modelling and optimization of the plasma reactor system for both non catalytic and catalytic dielectric barrier discharge plasma reactors. It was found that the catalytic dielectric barrier discharge plasma reactor performed better performance than the non-catalytic one and the conventional fixed bed reactor. The main products from the plasma reactor were ethane, carbon monoxide, propane, and hydrogen, while the minor products were ethylene and acetylene.